The role of mediation resources in the operation and development of knowledgeintensive small and medium enterprises - Köpeczi-Bócz, Tamás; Lőrincz, Mónika (Acta Agraria Debreceniensis, 2016)
Address social and economic processes of social capital system between universities and the business sector – because of their special and similar characteristics – major emphasis will be displayed. Knowledge-intensive companies would be hard to imagine functioning without established links with tertiary education institutions and universities can now functions would be unthinkable without displaying the corporate sector sectoral specificities of knowledge and strategies of the university. Because of the development of knowledge-intensive business activities based on innovation-oriented economic development which are specific to innovative SMEs, funding sources and opportunities. In a typical operating environment of innovation, with sectoral, spatial and temporal factors are constantly changing. These factors are decisive elements in the innovation opportunities, and through this indirectly the success of these enterprises. The resources involved in mediating the markets perceive a high risk to price this innovation activities and their funding. Under the study to try to answer that by optimizing the functions of universities, how and in what form they may have a role in mitigating financial risks.